Sistem Informasi Pusat Karir dan Tracer Study di Muhammadiyah Sidoarjo Berbasis Mobile - Prasetyo, Teguh; Eviyanti , Ade (Journal of Technology and System Information, 2024)
Muhammadiyah Sidoarjo University is one of the tertiary institutions in the Sidoarjo region with quite good accreditation, every year graduating thousands of students. In managing alumni data, it is necessary to have a career center and tracer study to trace alumni's footsteps to achieve qualifications according to market needs. Alumni tracking has been carried out by Universitas Muhammadiyah Sidoarjo through a website-based application, from the observation of the author the application currently running still has many shortcomings including there are still many students who do not fill out surveys as alumni biodata. Therefore it is necessary to develop an information system that can help the campus to collect alumni data more accurately. The objectives of this study were to create a mobile-based career information system and tracer study center, to make it easier for the campus to know the quality and quantity of alumni whether the jobs obtained are in accordance with their areas of expertise. This research uses the prototype development method and the system design method uses Unified modeling. The Modeling Language (UML), as well as its implementation, uses the Kotlin programming language and Android Studio and MYSQL as the databases. The results of this research are in the form of a Mobile-Based Career Center and Tracer Study Information System at the Muhammadiyah University of Sidoarjo which is expected to facilitate the process of managing alumni data